One round of azithromycin MDA adequate to interrupt transmission in districts with prevalence of trachomatous inflammation-follicular of 5.0-9.9%: Evidence from Malawi. - Khumbo Kalua; Alvin Chisambi; David Chinyanya; Michael Masika; Ana Bakhtiari; Rebecca Willis; Paul M Emerson; Anthony W Solomon; Robin L Bailey (PLoS Neglected Tropical Diseases)
Background As highly trachoma-endemic countries approach elimination, some districts will have prevalences of trachomatous inflammation-follicular in 1-9-year-olds (TF1-9) of 5.0-9.9%. The World Health Organization (WHO) previously recommended that in such districts, TF prevalence be assessed in each sub-district (groupings of at least three villages), with three rounds of azithromycin treatment offered to any sub-district in which TF≥10%. Given the large number of endemic districts worldwide and the human and financial resources required to conduct surveys, this recommendation may not be practical. In a group of 8 Malawi districts with baseline TF prevalences of 5.0-9.9%, the Malawi Ministry of Health administered one round of azithromycin mass treatment, to the whole of each district, achieving mean coverage of ~80%. Here, we report impact surveys conducted after that treatment. Methods We undertook population-based trachoma surveys in 18 evaluation units of the 8 treated districts, at least 6 months after the MDA. The standardized training package and survey methodologies of Tropical Data, which conform to WHO recommendations, were used. Results Each of the 18 evaluation units had a TF1-9 prevalence <5.0%. Conclusion The study demonstrates that in Malawi districts with TF of 5.0-9.9%, one round of azithromycin MDA with ~80% coverage associates with a reduction in TF prevalence to <5%. Further evidence for this approach should be collected elsewhere.